Implications of employee's perception of the role and activity of the human resources department in Romanian tourism & hospitality industry - Abrudan, Maria Madela (Array, 2008)
Summary: This paper is focused on the results of a study which has as main objective the assessment of the perception that employees have on the activity and the role of the Human Resources Department in Romanian Tourism and Hospitality Industry. The study was based on the administration of a questionnaire designed especially for this purpose addressed to the employees. The dimensions included in the questionnaire: a) The role of the HR Department from the employees' perspective b) Typical activities of the HR Department from the employees' perspective c) The relationship of the HR Department with the employees – trust and interaction d) The investment in employees– the development of the employees